PPUPIK Unit Produksi Mesin Otomatis bagi UMKM Pangan untuk Meningkatkan Standar Mutu Produk Pangan - Harsawardana Harsawardana; Maria Ulfah; Bayu Samodra; Antonius Budi Suharyono (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
This campus intellectual product business development activity aims to develop a Pilot Plan and workshop business as a production center for agro-industrial machinery and equipment that can provide opportunities and work experiences to students of the Agricultural Engineering Study Program, Stiper Agricultural University and encourage the development of an environmen utilizing research results from the lectures and researchers at the Stiper Agricultural University. Another objective is to transfer agro-industrial technology to small and medium-scaled industries and cooperatives in the food sector. PPUPIK programs is focusing on service activities, production of automatic machine and equipment for small-scaled food industry. Even though the program could need the demand of other agro-industries. The methods of implementing this activity are training, consultation, machine and equipment fabrication, as well as feasibility testing of agro-industrial machines and equipment. Through this activity, it has succeeded in establishing a business institution to increase campus income and entrepreneurial training places for final semester students and has succeeded in producing and selling 17 units of agro-industrial equipment machines and has held four trainings from May 2019 to the month July 2020.DOI: https://doi.org/10.26905/abdimas.v5i3.4662